Interpersonal emotion regulation in young adults with low and high psychosis proneness: a diary study - Riehle, Marcel; Brauer, Saskia; Lincoln, Tania; Prüßner, Luise (Cognitive therapy and research, 2024)
Emotion regulation is a complex process that often involves the presence of others, also known as interpersonal emotion regulation (IER). However, little is known about how psychotic symptoms relate to IER. We investigated whether young adults with elevated psychosis proneness engage in IER less frequently and find it less helpful than those with low psychosis proneness.